H∞ Estimation for a Class of Lipschitz Nonlinear Discrete-Time Systems with Time Delay. (17th July 2011) - Zhao, Huihong; Zhang, Chenghui; Wang, Guangchen; Xing, Guojing
Abstract : The issue ofH ∞ estimation for a class of Lipschitz nonlinear discrete-time systems with time delay and disturbance input is addressed. First, through integrating theH ∞ filtering performance index with the Lipschitz conditions of the nonlinearity, the design of robust estimator is formulated as a positive minimum problem of indefinite quadratic form. Then, by introducing the Krein space model and applying innovation analysis approach, the minimum of the indefinite quadratic form is obtained in terms of innovation sequence. Finally, through guaranteeing the positivity of the minimum, a sufficient condition for the existence of theH ∞ estimator is proposed and the estimator is derived in terms of Riccati-like difference equations. The proposed algorithm is proved to be effective by a numerical example.